Effect of sintering temperature on the chemical bonding, electronic structure and electrical transport properties of β-Ga1.9Fe0.1O3 compounds. (20th March 2021) - Roy, Swadipta; Ramana, C.V.
Abstract: A model system, which is based on iron (Fe) doped gallium oxide (Ga2 O3 ) (Ga1.9 Fe0.1 O3 ), has been considered to elucidate the combined effect of transition-metal ion doping and processing temperature on the chemistry, local structure and chemical bonding, and electrical transport properties of a wide band gap oxide (Ga2 O3 ). The Ga1.9 Fe0.1 O3 compounds were synthesized using standard high-temperature solid state reaction method. The effect of processing conditions in terms of different calcination and sintering environments on the structural and electrical properties of Ga1.9 Fe0.1 O3 compounds is studied in detail. Structural characterization by Raman spectroscopy revealed that Ga1.9 Fe0.1 O3 compounds exhibit monoclinic crystal symmetry, which is quite similar to the intrinsic parental crystal structure, though Fe-doping induces lattice strain. Sintering temperature (Tsint ) which was varied in the range of 900−1200 °C, has significant impact on the structure, chemical bonding, and electrical properties of Ga1.9 Fe0.1 O3 compounds. Raman spectroscopic measurements indicate the proper densification of the Ga1.9 Fe0.1 O3 compounds achieved through complete Fe diffusion into the parent Ga2 O3 lattice which is evident at the highest sintering temperature. The X-ray photoelectron spectroscopy validates the chemical states of the constituent elements in Ga1.9 Fe0.1 O3 compounds. The electrical properties of Ga1.9 Fe0.1 O3 fully controlled by Tsint, which governed the grain size and microstructural evolution. The temperature and frequency dependent electrical measurements demonstrated the salient features of the Fe doped Ga2 O3 compounds. The activation energy determined from Arrhenius equation is ∼0.5 eV. The results demonstrate that control over structure, morphology, chemistry and electrical properties of the Ga1.9 Fe0.1 O3 compounds can be achieved by optimizing Tsint .